Sustainability Of Fishermen's Economy Post-Implementation Of Government Regulation No. 85 Of 2021 On Types And Tariffs On Non-Tax Acceptance Types - Panji hendrarso; Rudianto, Rudianto; Ryska Hadianti; Jumanah, Jumanah (Jurnal Scientia, 2024)
This research aims to discuss the impact and implications of Government Regulation Number 85 of 2021 on the economic sustainability of fishermen in Indonesia by regulating the sustainable management of fish resources. The issue focuses on discussing how this regulation affects the economic sustainability of fishermen, including its impact on income, welfare and The survival of fishermen. In order to approach this problem, references are used. Data was collected through descriptive research with a qualitative approach, namely a form of research that aims to provide a general overview of various types of data collected from the field objectively. This study concludes that regarding the size of the PNBP increase rate for fishermen of around 5-10 percent, we can analyze the contents of the regulations, their impact on fishermen and fisheries entrepreneurs, as well as responses and recommendations related to these regulations and so that these regulations can have an impact on economic progress and the welfare of the actors. business in the fisheries sector by looking at fish prices in very different regions. From the results of this study, the author concludes that the burdensome regulations are regarding the size of the PNBP increase rate for fishermen of around 5-10 percent. Apart from that, the existence of this PP is considered a policy that does not involve the public, in this case fishermen and fisheries business actors. For this reason, fishermen and fisheries business actors demand legal certainty and freedom of business that does not burden them.